(untitled) (Ustozlar uchun, 2025)
Romanticism, which emerged in the late 18th century, marked a radical break from the rationality and order of the Enlightenment and introduced new aesthetic, philosophical, and literary perspectives. This article examines the core themes and innovations of English Romanticism, focusing on the works of major poets such as William Wordsworth, Samuel Taylor Coleridge, Lord Byron, Percy B. Shelley, and John Keats. The study highlights Romanticism’s emphasis on individuality, imagination, nature, emotion, and the sublime. Additionally, it explores the movement’s formal experiments, including new poetic diction, the rise of lyrical poetry, and the reconstruction of the poet’s role in society. The findings contribute to a deeper understanding of how Romantic writers transformed English literature and shaped modern literary thought.